Sexuality among 7th, 8th and 9th grade students in the state of Lara, Venezuela. The Global School Health Survey, 2003-2004 - Granero, Ricardo; Poni, Esteban S.; Sánchez, Zoraida (Puerto Rico Health Sciences Journal, 2009)
Background: Effective sexual health promotion programs need to be based on evidence; this study describes a set of sexual behavioral patterns, education and other subjects related to sexual life among 7th, 8th and 9th grade students in the State of Lara, Venezuela. Methods: During 2003 to 2004 school period, 2070 students filled out the Global School Health Survey (GSHS) –a school based cross-sectional selfadministered survey that explores, among other areas, sexual behavior. Results: Students who responded that ever had intercourse, males 27% and females 3.8%; by grade, males 18.2% (7th) and 37.6 % (9th), and females 1.9% (7th) and 6.2% (9th). The group who had intercourse, 54.9% males and 25.3% females had it by age 12; 59% males and 78.6% females were sexually active in the past 12 months; 59.2% males and 43.2% females used condom in the last intercourse; and 48.3% males and 21.5% females has 2 or more sexual partners in their life. A disparity is present in school-based information, &#62 63% for AIDS and &#60 32% for sexual abuse. Conclusions: This study shows that a substantial number of students had sexual intercourse initiation at early age (&#60 12), history of multiple sexual partners and low prevalence of condom use. An unbalanced coverage of information on AIDS and sexual abuse is highly prevalent in the school. However, the implementation and evaluation of comprehensive programs on healthy sexual life must take into account that still a majority of students report abstinence from sexual intercourse.